Identification of 7–9 ring polycyclic aromatic hydrocarbons in coals and petrol coke using High performance liquid chromatography – Diode array detection coupled to Atmospheric pressure laser ionization – Mass spectrometry (HPLC-DAD-APLI-MS). (September 2019) - Thiäner, Jan B.; Nett, Linus; Zhou, Shangbo; Preibisch, Yves; Hollert, Henner; Achten, Christine
Abstract: Polycyclic aromatic hydrocarbons containing at least 24 carbon atoms (≥C24 -PAH) are often associated with pyrogenic processes such as combustion of fuel, wood or coal, and occur in the environment in diesel particulate matter, black carbon and coal tar. Some of the ≥C24 -PAH, particularly the group of dibenzopyrenes (five isomers, six aromatic rings) are known to show high mutagenic and carcinogenic activita. Gas chromatography – mass spectrometry is a well-established method for the analysis of lower molecular weight PAH but is not optimally suited for the analysis of ≥C24 -PAH due to their low vapor pressures. Also, hundreds of ≥C24 -PAH isomers are possible but only a few compounds are commercially available as reference standards. Therefore, in this study, a combination of multidimensional liquid chromatography, UV–Vis diode array detection, PAH selective and highly sensitive atmospheric pressure laser ionization – mass spectrometry is used to detect and unequivocally identify PAH. For identification of PAH in two bituminous coals and one petrol coke sample, unique and compound specific UV–Vis spectra were acquired. It was possible to identify ten compounds (naphtho[1, 2, 3, 4- ghi] perylene, dibenzo[ b, ghi ]perylene, dibenzo[ e, ghi ]perylene, dibenzo[ cd, lm ]perylene, benzo[ a ]coronene, phenanthrol[5, 4, 3, 2- abcde ]perylene, benzo[ ghi ]naphtho[8, 1, 2- bcd ]perylene, benzo[ pqr ]naphtho[8, 1, 2- bcd ]perylene, naphtho[8, 1, 2- abc ]coronene and tribenzo[e, ghi, k ]perylene) by comparison of acquired spectra with spectra from literature. Additionally, it was possible to detect similar distribution patterns in different samples and signals related to alkylated naphthopyrenes, naphthofluoranthenes or dibenzopyrenes. Subsequent effect-directed analysis of a bituminous coal sample using the microEROD (ethoxyresorufin- O -deethylase) bioassay showed high suitability and revealed lower EROD induction for the ≥C24 -PAH (TEQ range 0.67–10.07 ng/g) than for the allover < C24 -PAH containing fraction (TEQ 84.00 ng/g). Nevertheless, the toxicity of ≥C24 -PAH has a significant impact compared with 24 -PAH and must be considered for risk assessment. The LC-DAD-APLI-MS method, presented in this study, is a powerful tool for the unequivocal identification of these ≥ C24 -PAH. Graphical abstract: Image 1 Highlights: First combination of DAD and APLI-MS for sensitive and isomer specific PAH detection. First compound identification of ≥C24 -PAH in bituminous coals and petrol coke. Dibenzo[ b, ghi ]perylene quantified in bituminous coals and petrol coke. Up to 489 peaks related to alkylated dibenzopyrenes and naphthofluoranthenes detected. Comparatively low EROD induction in ≥C24 -PAH fractions. Abstract : PAH with at least 24 C atoms were identified in petrogenic matrices by UVVis spectra in combination with highly sensitive and selective APLI – mass spectrometry.